Alternative Dispute Resolution: A Business (and) Communication Strategy - Netzley, Michael A. (Institutional Knowledge at Singapore Management University, 2001)
This article presents an interview with Michael Landrum and Cynthia Waters, two attorneys concerning the application of alternative dispute resolution (ADR) as a business and communication strategy. Landrum is a founding partner of labor and employment law practice representing management Burk & Landrum. Waters, is an attorney and mediator. The two attorneys offered learning points and skills that must be taught to business students concerning managing disputes.